A disputa de Fernando Haddad e Jair Bolsonaro à presidência do Brasil em 2018: análise argumentativa persuasiva das estratégias discursivas no instagram - Ribeiro, Andressa Dembogurski (2020)
We understand that we live in a society in which the media permeates various fields and changes their configurations in the face of technological developments. Taking into account this scenario, we propose to contribute with the thoughts regarding the communicative activities, more precisely the advertising ones, in relation to the strategic construction of the electoral campaigns. In this context, we also understand the importance of image as an argumentative and persuasive element, where we no longer identify the boundaries of political discourse and propagandist discourse in a communicational process that is mainly composed of emotion. This debate leads us to propose an understanding on this subject by identifying the discursive strategies employed by candidates Fernando Haddad and Jair Bolsonaro during the 2018 Instagram election campaign. This through the Persuasive Argumentative Analysis protocol that we created from Charaudeau's (s / d, 2010, 2016, 2017) conceptualizations about discourse, and from Roque (2016) and Barthes (2000) about the image. And also through a theoretical construction that permeates the affects of publicity and political propaganda (Habermas, 2014; Sant'anna, Junior, Garcia, 2010; Neusa Gomes, 1997, 2004, 2008; Wilson Gomes, 2004; Albuquerque, 2005) and the concept of advertising (Casaqui, 2011, 2014, 2019; Romeyer, 2015); besides studies that allow us to understand how electoral campaigns have evolved through the emergence of new media (Utida, 2011; Salgado, 2012; Iasulaitis, 2015; Panke and Cervi, 2011; Panke et al., 2011; Bozza and Panke, 2013; Norris, 2000; Marques, 2016; Massuchin and Tavares, 2011; and Miguel and Biroli, 2011; Gomes et al., 2009; Marques and Sampaio, 2013; Aggio, 2013; Ituassu et al., 2018 ; Braga; Carlomagno, 2019; Malini, 2018; Marques, 2018). Finally, it is understood in this process that the image is one of the elements of discourse and that, along with other tools of political and propagandist discourse, integrates communicational making through argumentative and persuasive / emotional devices enhanced by the use of social networks, in this case Instagram, which for m what we identify as publicizing politics.